2019
DOI: 10.1123/jmld.2018-0041
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Fundamental Movement Skills of 3- to 5-Year-Old Children in Irish Preschool Services

Abstract: The aim of this study was to quantify levels of physical activity (PA) and fundamental movement skills (FMS) of children aged 3 to 5 years in Irish preschool services during care hours, and investigate the relationship between these two variables. Data were collected from 141 children (50.3% boys, age M = 3.9 ± 0.5 years) across 9 preschool services. Measurements included PA via accelerometry, and proficiency in four FMS (run, vertical jump, throw and catch). The recommended guideline of 15 minutes of PA per h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 76 publications
1
15
0
Order By: Relevance
“…A common theme found between the motor proficiency performance of the children was the majority of authors reporting locomotor skills being performed with more competency than object control skills at this age [ 46 , 47 , 50 , 53 ] and, similarly, both Duff et al [ 47 ] and Jones et al [ 48 ] found running to be the most proficient individual skill at this age over any other individual locomotor or object control skill tested. On the other hand, only Palmer et al [ 51 ] found the opposite in their baseline assessments, with object control skills being performed with more proficiency.…”
Section: Resultsmentioning
confidence: 89%
See 4 more Smart Citations
“…A common theme found between the motor proficiency performance of the children was the majority of authors reporting locomotor skills being performed with more competency than object control skills at this age [ 46 , 47 , 50 , 53 ] and, similarly, both Duff et al [ 47 ] and Jones et al [ 48 ] found running to be the most proficient individual skill at this age over any other individual locomotor or object control skill tested. On the other hand, only Palmer et al [ 51 ] found the opposite in their baseline assessments, with object control skills being performed with more proficiency.…”
Section: Resultsmentioning
confidence: 89%
“…Of the ten articles reviewed, three articles used the full TGMD-2 protocol and scored this against the TGMD-2 criteria [ 44 , 45 , 46 ]. A further three articles used a version of the TGMD-2 protocol adapted for use within individual studies [ 47 , 48 , 49 ]. This included using specific skills, removal of unwanted or unwarranted skills and addition of more relevant skills related to the study outcomes or cultural differences.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations